Spinal Anesthesia Does Not Impact Prostate Cancer Recurrence in a Cohort of Men Undergoing Radical Prostatectomy: An Observational Study - Tseng, Kenneth S. (2014)
BACKGROUND AND OBJECTIVES: Prior studies suggest a possible association between the use of neuraxial-general anesthesia and a decrease in prostate cancer recurrence after radical prostatectomy. We examine the correlation of a spinal anesthesia-only technique on prostate cancer recurrence. METHODS: Charts from consecutive radical prostatectomy patients of 3 experienced urologists from January 1999 to December 2005 were reviewed. In addition to the usual clinical and pathologic predictors of disease recurrence, patient records were queried for the type of anesthesia (general versus spinal) performed. A Cox proportional hazards model was used to determine the statistical significance of predictors of biochemical recurrence. RESULTS: A total of 1,964 patients—1,166 and 798 receiving spinal with sedation or general anesthesia, respectively—had complete preoperative and follow-up data. In univariate proportional hazards analysis, the use of general anesthesia was associated with a trend towards an increased risk of biochemical recurrence when compared with the use of spinal anesthesia (hazard ratio = 1.29, 95% confidence interval [CI] 0.99–1.66, P=0.053). In multi-variable analysis, the effect size (hazard ratio = 1.10, 95% CI 0.85–1.42, P=0.458) was diminished by clinical and pathologic variables. CONCLUSIONS: This was a retrospective study of patients with prostate cancer who have undergone radical prostatectomy during a time period when the practice of anesthesia for prostatectomy at our institution was transitioned from spinal to general anesthesia. In our study, when controlling for other predictors of advanced prostate cancer, the type of anesthetic given during prostatectomy had no effect on the risk of biochemical recurrence.